Concentrations of some heavy and trace metals in serum and brain of five species of wild vertebrates from Nigeria - Igado Olumayowa Olawumi; Olopade Funmilayo Eniola; Gilbert Taidinda Tashara; Obasa Adedunsola Adewunmi; Omile Irene Chizubelu; Peter-Ajuzie Iheanyi Kemdirim; Adedokun Kehinde Iyanuoluwa; Olopade James Olukayode (Folia Veterinaria)
Environmental pollution from heavy metals is a growing concern, largely driven by increased industrial activity. This study measured the concentrations of seven heavy metals—lead, cadmium, chromium, manganese, cobalt, copper, and iron—and two trace metals—magnesium and nickel—in the serum, cerebrum, cerebellum, and brainstem of the hedgehog (Eulipotyphla), pigeon (Columbiformes), cattle egret (Pelecaniformes), and two species of squirrel (Sciuromorpha), using Atomic Absorption Spectrophotometry. Among the metals tested, magnesium showed the highest concentrations across all sample types and brain regions in all studied animals. Magnesium levels reached as high as 817,598 µg/mL in the serum of female pigeons. Metal levels were generally higher than those reported in previous studies from other regions, except for cobalt, which was undetectable in the tested tissues. The highest concentrations for all metals were found in the serum. No consistent pattern was observed in metal concentrations across the brain regions. These findings reveal complex patterns of metal accumulation and distribution, potentially reflecting interspecies differences in physiology, diet, and environmental exposure. The data offers insights into metal presence in wildlife serum and brains. It will also provide crucial baseline dataset with information that can be invaluable for future ecological and environmental studies.